Marketplace Pemasaran Produk Pertanian Berbasis Mobile Menggunakan Pendekatan Waterfall - Asyhar Qowiim; Adityo Permana Wibowo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The current agricultural industry is still minimal in utilising technology so that limited access to information related to market demand and means of direct sales to consumers is a major obstacle in improving the welfare of farmers. The distribution process of agricultural products is still carried out conventionally through direct interaction, making it less effective and efficient. The development of information and communication technology, especially in the use of mobile devices, provides new opportunities to overcome existing problems. This research aims to solve the existing problems by creating a mobile-based application to increase sales of agricultural products. The application is developed using the waterfall approach method with several stages such as needs analysis, design, implementation, testing to maintenance. Flutter programming language is also used in coding the application system. Based on the design and implementation carried out in this study, an application is produced with features that display products and effective payment features. The existing features are then tested by 30 respondents with the black box testing method and the results obtained are 100% the application can run well. The application can increase transparency and efficiency in the sale of agricultural products. The application also provides convenience for farmers as consumers.